SIMPLE ADDITIVE WEIGHTING FOR MODELING DSS TO DETERMINE THE BEST COLLEGE IN PRINGSEWU - Elisabet Yunaeti Anggraeni; Widi Andewi; Oktafianto Oktafianto (IJISCS (International Journal of Information System and Computer Science), 2017)
Continuing study to a college is a hope for prospective students. However, that is an easy problem, because that needs to be considered in choosing such as, the cost during the lecture took place, facilities, facilities and infrastructure, cooperation between universities and others. By using The Decision Support System, the calculation of all criteria can be able to determine the best college to assist prospective students in selecting and choosding the college. The Decision Support System uses the Simple Additive Weighting (SAW) method. The Decision Support Issues are basically for the selection of alternative actions enabling prospective students in choosing the college which they want, and will produce a best decision for prospective students for continuing in the best collage.